2019
DOI: 10.1111/liv.14108
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of cigarette smoking on liver fibrosis and its regression under therapy in male patients with chronic hepatitis B

Abstract: Background & Aims:The role of cigarette smoking in the development of chronic hepatitis B (CHB) remains poorly understood. We assessed the potential contributions of cigarette smoking to liver fibrosis and its regression after starting antiviral therapy in CHB patients. Methods:In this cohort study, 2144 consecutive male CHB patients under no antiviral therapy were evaluated and 206 patients with significant liver fibrosis (≥F2) initiating antiviral therapy had longitudinal follow-up. Liver fibrosis was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Smoking was categorized as with or without a smoking history (20). Alcohol use was categorized as with a significant drinking history (>20 g/d) or without.…”
Section: Methodsmentioning
confidence: 99%
“…Smoking was categorized as with or without a smoking history (20). Alcohol use was categorized as with a significant drinking history (>20 g/d) or without.…”
Section: Methodsmentioning
confidence: 99%
“…In this cross-sectional study of patients with chronic HCV, higher consumption of tobacco measured by smoking pack-years was related to greater severity of fibrosis [15]. Further, Xiong et al [16] found that a cigarette smoking history of 10 pack years or greater was associated with advanced fibrosis in chronic hepatitis B (CHB) infection and impaired fibrosis regression with CHB treatment. The present study found that the relationship between smoking and hepatic fibrosis was also significant after HCV clearance.…”
Section: Discussionmentioning
confidence: 80%
“…The toxic and harmful substances produced by smoking can damage the antioxidant system, including cytochrome P450 and inflammatory cytokines [33]. Although the effects of smoking on CHB infection and cirrhosis have been reported [17, 34, 35], there is limited information on the relationship between smoking and NAFLD. Hamabe et al [19] reported that smoking is an independent risk factor for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…It can damage the antioxidant system [14, 15]. Although smoking can increase the risk for liver fibrosis and cirrhosis in patients with chronic hepatitis B (CHB) infection [16, 17], only a few studies have investigated the relationship between smoking and NAFLD. Suzuki et al [18] reported that smoking is associated with high levels of alanine aminotransferase (ALT) in patients with NAFLD.…”
Section: Introductionmentioning
confidence: 99%